Chronic traumatic encephalopathy (CTE) is absent from a European community-based aging cohort while cortical aging-related tau astrogliopathy (ARTAG) is highly prevalent. (May 2021) - Forrest, SL; Kril, JJ; Wagner, S; Hönigschnabl, S; Reiner, A; Fischer, P; Kovacs, GG
Abstract : Chronic traumatic encephalopathy (CTE) and aging-related tau astrogliopathy (ARTAG) are characterised by tau-immunopositive neuronal and/or astrocytic inclusions, with overlapping cortical involvement and astrocytic inclusion morphology. This study determined the prevalence of CTE and cortical ARTAG in a European community-based population (n=310) and explored overlap of both pathological entities. Frontal, parietal and temporal cortices were assessed. No case fulfilling CTE criteria was found. However, isolated astroglial or neuronal tau pathologies were recognized in sulcal depths (<2%). One case without history of traumatic brain injury showed combined tau-immunoreactive features confined to frontal sulci without perivascular accumulation. Another 24 cases had single tau pathologies in cortical sulci. ARTAG was identified in 117 cases (38%), with a similar regional prevalence. Grey matter ARTAG was the most common followed by subpial, white matter and perivascular. The presence of any type of ARTAG was associated with having another type of ARTAG in the same region ( P <0.05). In summary, cortical ARTAG in this population is common and contrasts the high prevalence of CTE in individuals with repeated mild traumatic brain injury. LEARNING OBJECTIVES: This presentation will enable the learner to: Classify tau-immunopositive astrocytic inclusions characteristic of ARTAG 1. Describe neuropathological components of CTE 2. Identify CTE and cortical ARTAG in a case series